Water, food and poverty: Global- and basin-scale analysis - Cook, Simon; Fisher, M.; Tiemann, T.; Vidal, A. (Routledge, Taylor & Francis Group, 2011)
Global population growth exerts stresses on river basins that provide food, water, energy and other ecosystem services. In some basins, evidence is emerging of failures to satisfy these demands. This paper assembles data from nine river basins in a framework that relates water and food systems to development. The framework provides a consistent basis for analysis of the water and food problem globally, while providing insight into specific conditions within basins. The authors find that successes occur when demand is met by increased productivity, while failure occurs when factors conspire to prevent development of land and water resources. © 2011 International Water Resources Association.